Ethical economics and sustainable development - Maréchal, Jean-Paul (Sens public)

(untitled) (Département des littératures de langue française, 2008)
The law of the jungle – is this all the future holds for us? Unfortunately, reading some opinion articles we might believe that this is inevitably the case. In 1984, the year in which Gérard Debreu was awarded the Nobel Prize in Economics, he said in le Figaro Magazine that the superiority of liberalism had been proven mathematically, bearing in mind, that just as a few decades earlier, the brilliants minds of the time had also given “scientific” socialism the stamp of approval. Closer to our time, in 2003, the then [French] Finance Minster, Francis Mer, argued on a television programme that a person’s salary was proportional to his value in society. Taken literally, his statement implies that a Managing Director with a salary of 38.8million euros is by far more useful to society than either, a carer, teacher or judge. The facts show that, two decades down the line, the economist and ex-business leader’s comments mirror the current situation to the point that we might believe that market law can harmonize economic efficiency and social justice perfectly.